Approaches to Islamic Educational Supervision: A Theoretical Study and Adaptive Implementation in Improving Learning Quality: PENDEKATAN SUPERVISI PENDIDIKAN ISLAM: KAJIAN TEORITIS DAN IMPLEMENTASI ADAPTIF DALAM PENINGKATAN MUTU PEMBELAJARAN - Anta Ibnu Marzuq Arum; Ali Muhdi (STKIP Subang, 2026)
This study aims to analyze Islamic education supervision approaches, namely directive, non-directive, collaborative, and scientific approaches, theoretically and their adaptive implementation in improving learning quality in Indonesian educational institutions. Using a Systematic Literature Review (SLR) method, this study systematically collected and analyzed 30 relevant sources from national and international academic databases, covering the period 2019–2026. The inclusion criteria encompassed peer-reviewed articles, books, theses, and government regulations related to educational supervision in the Indonesian context. Data analysis was conducted through thematic synthesis by identifying key themes from selected literature. The findings show that each approach has distinct strengths and limitations: the directive approach is effective for beginning teachers with low competency; the non-directive approach promotes professional autonomy for experienced teachers; the collaborative approach builds a professional learning community, while the scientific approach strengthens the objectivity and accountability of supervision through data utilization. In the post-pandemic context facing learning loss and the Merdeka Belajar policy, no single approach is universally superior. This study recommends an Integrative Adaptive Supervision model that combines all four approaches flexibly based on teacher developmental levels, integrating Islamic values—shura, amanah, adl, and ihsan—as ethical filters throughout the supervision process. This model is considered most suitable for the plural Indonesian educational context, especially Islamic educational institutions such as madrasah and Islamic boarding schools. Keywords: